Pengaruh Media Pembelajaran Audio Visual Dan Variasi Mengajar Guru Terhadap Hasil Belajar Siswa Kelas IX Mata Pelajaran IPS SMP Negeri 11 Pematangsiantar - Dita Dyftania Arga Simanjuntak; Debbi Petra Meyana Sitorus; Binsar Tison Gultom (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research aims to determine the "Influence of Audio Visual Learning Media and Teacher Teaching Variations on the Learning Outcomes of Class IX Students in Social Sciences Subjects at SMP Negeri 11 Pematangsiantar for the 2023/2024 Academic Year." This type of research is quantitative research with a quantitative descriptive data analysis approach. The research population was 45 Class IX Social Sciences Subjects at SMP Negeri 11 Pematangsiantar. The research sample was 45 people. The sampling technique used was a saturated sampling technique. The data collection technique used was a questionnaire. The hypothesis testing technique uses multiple linear regression analysis and the coefficient of determination (R2). The results of the research are that there is no significant influence between audio-visual media on the learning outcomes of class . Meanwhile, variations in teacher teaching have a significant influence on the learning outcomes of class. The results of the F test show that the significance value for the influence of X_1 and And it can also be seen that the R Square value is 0.171. So it can be concluded that audio visual media and variations in teacher teaching have a simultaneous or joint effect on learning outcomes by 17.1%.